2018
DOI: 10.4314/ajcem.v20i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of anti-HCV antibody amongst in-school youth in a Nigeria university

Abstract: Infection with Hepatitis C Virus (HCV) is a public health problem. Worldwide, there are about 170 million people infected with HCV. HCV is transmitted through sex and use of contaminated sharp objects during tattooing or intravenous drug abuse. These routes make youth to be more vulnerable. Transfusion and mother to child transmissions are also documented modes. This study was carried out to determine sero-prevalence of hepatitis C virus infection among in school youth at Achievers University, Owo in southwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…Pakistan and NursingCollege Students of Central India indicated to have knowledge and awareness of HBV infection as reported by Ghouri et al[38] and Mahore et al[39], respectively.With regard to HCV infection, a zero (0%) prevalence rate was recorded in this current study as none of the participants were positive for antibody to Hepatitis C Virus (anti-HCV). This agrees with the work of Muhibi et al[40] and Alquatani et al[24], who both reported zero (0%) prevalence of anti-HCV antibody among undergraduate students of Achievers University, Owo in south-west Nigeria, as well as among Health Students in the Najran region of South-Western Saudi Arabia, respectively. The outcome of this study however differ slightly from the work of Hebo et al[23] who reported a prevalence of 0.42% among Health Workers of University Medical Center, Southwest Ethiopia, as well as that of Jemilohun et al[41] who reported a prevalence rate of 0.40% among undergraduate Student of Ladoke Akintola University of Technology (LAUTECH), Ogbomosho, Oyo State, south-west Nigeria.…”
supporting
confidence: 92%
“…Pakistan and NursingCollege Students of Central India indicated to have knowledge and awareness of HBV infection as reported by Ghouri et al[38] and Mahore et al[39], respectively.With regard to HCV infection, a zero (0%) prevalence rate was recorded in this current study as none of the participants were positive for antibody to Hepatitis C Virus (anti-HCV). This agrees with the work of Muhibi et al[40] and Alquatani et al[24], who both reported zero (0%) prevalence of anti-HCV antibody among undergraduate students of Achievers University, Owo in south-west Nigeria, as well as among Health Students in the Najran region of South-Western Saudi Arabia, respectively. The outcome of this study however differ slightly from the work of Hebo et al[23] who reported a prevalence of 0.42% among Health Workers of University Medical Center, Southwest Ethiopia, as well as that of Jemilohun et al[41] who reported a prevalence rate of 0.40% among undergraduate Student of Ladoke Akintola University of Technology (LAUTECH), Ogbomosho, Oyo State, south-west Nigeria.…”
supporting
confidence: 92%
“…However, the studies were done in different regions with different population demographics. In another study done among students of Achievers University Idashen, Owo, in south-western Nigeria involving 70 respondents, the seroprevalence of hepatitis-C was 0% [13] similar to our finding. This could also be due to the small number of responds involved in the study.…”
Section: Discussionsupporting
confidence: 90%